The Good Governance Principle in Fictitious-Positive Case Applications After the Job Creation Law - Dewi Cahyandari (Yustisia, 2023)
The enactment of Law Number 30 of 2014 expands the competence of the State Administrative Court in protecting members of the public but also state administrators. Law Number 6 of 2023 concerning Job Creation (Law on Job Creation) mentions fictitious-positive cases in Article 175 number 6, which has changed the provisions on fictitious-positive cases. This study aims to see that the judiciary examines fictitious-positive cases after the enactment of the Job Creation Law and how the public submits requests for review of cases after the Act comes into effect. The research is normative and has a legal and philosophical approach. The research data consisted of primary and secondary materials. The authority of judges to examine fictitious-positive cases has been lost after the enactment of the Job Creation Law, reducing the use of the General Principles of Good Governance in reviewing fictitious-positive cases. However, the enforcement of the Job Creation Law seems to leave legal uncertainty for justice seekers regarding fictitious-positive matters, indicating that the reinstatement of the judiciary's authority to review applications for these fictitious-positive cases needs to be taken into account